Serpentine Supravenous Hyperpigmentation Following Intravenous Docetaxel - Satarupa Mondal; Avik Panigrahi; Dibyendu Bikash Bhanja; Sayantani Chakraborty; Abheek Sil (Wolters Kluwer Medknow Publications, 2021)
Serpentine supravenous hyperpigmentation is a rare, cutaneous sequela of intravenous chemotherapeutic agents, collagen vascular diseases (systemic sclerosis, systemic lupus erythematosus, and rheumatoid arthritis), and infections like leprosy and HIV. The condition manifests clinically as a peculiar, patterned eruption characterized by hyperpigmented streaks following the superficial venous network on the skin. Here, we report a case of a middle-aged lady with breast carcinoma, who developed serpentine supravenous hyperpigmentation after intravenous docetaxel.